Expansion of Immature Neutrophils During SIV Infection Is Associated With Their Capacity to Modulate T-Cell Function - Lemaitre, Julien; Desjardins, Delphine; Gallouët, Anne-Sophie; Gomez-Pacheco, Mario; Bourgeois, Christine; Favier, Benoit; Sáez-Cirión, Asier; Le Grand, Roger; Lambotte, Olivier (Frontiers in Immunology, 2022)
In spite of the efficacy of combinational antiretroviral treatment (cART), HIV-1 persists in the host and infection is associated with chronic inflammation, leading to an increased risk of comorbidities, such as cardiovascular diseases, neurocognitive disorders, and cancer. Myeloid cells, mainly monocytes and macrophages, have been shown to be involved in the immune activation observed in HIV-1 infection. However, less attention has been paid to neutrophils, the most abundant circulating myeloid cell, even though neutrophils are strongly involved in tissue damage and inflammation in several chronic diseases, in particular, autoimmune diseases. Herein, we performed a longitudinal characterization of neutrophil phenotype and we evaluated the interplay between neutrophils and T cells in the model of pathogenic SIVmac251 experimental infection of cynomolgus macaques. We report that circulating granulocytes consists mainly of immature CD10- neutrophils exhibiting a prime phenotype during primary and chronic infection. We found that neutrophil priming correlates with CD8+ T cell activation. Moreover, we provide the evidence that neutrophils are capable of modulating CD4+ and CD8+ T-cell proliferation and IFN-γ production in different ways depending on the time of infection. Thus, our study emphasizes the role of primed immature neutrophils in the modulation of T-cell responses in SIV infection.